Friction of human skin against smooth and rough glass as a function of the contact pressure - Derler, S.; Gerhardt, L.-C.; Lenz, A.; Bertaux, E.; Hadad, M. (Tribology international, 2009)
The friction behaviour of human skin was studied by combining friction measurements using a tri-axial force plate with skin contact area measurements using a pressure sensitive film. Four subjects carried out friction measurement series, in which they rubbed the index finger pad and the edge of the hand against a smooth and a rough glass surface under dry and wet conditions. The normal loads were varied up to values of 50 N, leading to skin contact pressures of up to 120 kPa. The analysis of the pressure dependence of friction coefficients of skin for contrasting sliding conditions allowed to determine the involved friction mechanisms on the basis of theoretical concepts for the friction of elastomers. Adhesion was found to be involved in all investigated cases of friction between skin and glass. If adhesion mechanisms predominated (skin against smooth glass in the dry condition and skin against rough glass in the wet condition), the friction coefficients were generally high (typically >1) and decreased with increasing contact pressure according to power laws with typical exponents between −0.5 and −0.2. Contributions to the friction coefficient due to viscoelastic skin deformations were estimated to be relatively small (<0.2). In those cases where the deformation component of friction played an important role in connection with adhesion (skin against rough glass in the dry condition), the friction coefficients of skin were typically around 0.5 and their pressure dependence showed weak trends characterised by exponents ranging from −0.1 to +0.2. If hydrodynamic lubrication came into play (skin sliding on smooth glass in the wet condition), the friction coefficients were strongly reduced compared to dry friction (<1), and their decrease with increasing contact pressures was characterised by exponents of <−0.7.